PENGGUNAAN MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) BERBANTUAN MEDIA GENIALLY DALAM MENINGKATKAN HASIL MENULIS TEKS DESKRIPSI PADA SISWA SMP KELAS VII - Siti Yulyasinta Lukmana Putri; Ika Mustika; Eli Syarifah Aeni (IKIP Siliwangi, 2026)
Descriptive text writing skills are still a challenge for junior high school students due to lack of motivation and varied learning models. Based on the background of the problem, this research is formulated on how the effectiveness of using the TGT (Teams Games Tournament) learning model assisted by Genially media in improving the results of writing description texts for junior high school students in grade VII. Then, how is the process of using the TGT model assisted by Genially media in improving the results of writing descriptive texts in VII grade junior high school students. This study aims to determine the process, improvement, and completeness of the results of writing description texts for junior high school students in grade VII through the application of the TGT (Teams Games Tournament) model assisted by Genially media. The research method used is descriptive quantitative to provide a clear picture objectively of the learning outcomes of writing description text. The data collection technique in this research is a test. The data analysis technique used descriptive statistics. The research method used is descriptive quantitative to provide a clear picture objectively of the learning outcomes of writing description text. The data collection technique in this research is a test. The data analysis technique used descriptive statistics. The results showed that the use of TGT model assisted by Genially media achieved an average score increased by 33% from 33% to 66% with sufficient category. Thus, learning by using the TGT model assisted by Genially media is said to be successful because students experience an increase from pretest to posttest. These results prove that with the use of the TGT model assisted by Genially media, students can more easily understand the description text material.